Medical shading breathable double-layer partition curtain and preparation method thereof
By using antibacterial polyester light-shading layer and viscose fiber fabric in medical blackout curtains, combined with the nanomaterial introduced by spray treatment, the problem of insufficient light-shading performance and breathability is solved, and a medical blackout and breathable double-layer wall with high efficiency light-shading, optimized breathability and antibacterial properties is achieved.
Patent Information
- Application Number
- CN202411689085.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing blackout curtains have problems with insufficient light-shading performance and breathability in medical places, and are easily soaked in disinfectant to cause bacteria to grow.
An antibacterial polyester light shielding layer is used as the base cloth, and carboxylated single-wall carbon nanotubes and tetrabutyl titanate are introduced through multiple spray treatments to form a conductive network to improve light shielding and antibacteriality. Viscose fiber fabric is used for hydrospuncture processing to form a gradient pore structure to optimize breathability.
It realizes efficient light-shading, optimized breathability and antibacterial properties of medical light-shading and breathable double-layer curtains, and ensures the effective use of the curtains in medical environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a medical light-shielding and breathable double-layer curtain and a preparation method thereof. Background Art
[0002] Blackout curtains have the function of blocking light and changing the light environment. In places such as hospitals where blackout and privacy are required, blackout curtains with good performance are usually required. Existing blackout curtains are mostly coated blackout cloth, multi-layer woven blackout cloth, jacquard blackout cloth, etc. Coated blackout cloth achieves the blackout effect by covering the gaps between the yarns of the fabric in a coating manner, but it is troublesome to process and feels hard; multi-layer woven blackout cloth has a black silk layer sandwiched in the middle layer to reduce the light-shielding rate of the fabric, and its weaving process is relatively complicated; jacquard blackout cloth improves the light-shielding performance of the fabric by increasing the tightness of the fabric, reducing the pores, and reducing the light transmittance of the fabric, but it affects the air permeability and has poor air permeability. In addition, medical curtains are often exposed to easily penetrated substances such as disinfectants, which can cause the presence of pathogens on the curtains. Summary of the invention
[0003] The purpose of the present invention is to provide a medical light-shielding and breathable double-layer curtain and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a medical light-blocking and breathable double-layer curtain, which is made of an antibacterial polyester light-blocking layer as the base fabric and a viscose fiber fabric as the surface layer, and is made by multiple spunlace processes.
[0005] Furthermore, the antibacterial polyester shading layer is made of high-density polyester warp-knitted fabric after three spraying treatments.
[0006] Furthermore, the polyester fiber specification in the high-density polyester warp-knitted fabric is 56dtex / 24F, and the transverse and longitudinal density of the fabric is (70-80)×(100-110) strands / inch.
[0007] Furthermore, the first spray treatment uses deionized water as the spray medium and sprays at a certain temperature; the second spray treatment uses carboxylated single-walled carbon nanotube-deionized water dispersion as the spray medium and sprays intermittently under ultrasound; the third spray treatment first uses tetrabutyl titanate ethanol as the spray medium, sprays for a period of time, and then uses ethanol-water-ammonia water as the spray medium and sprays at different temperatures.
[0008] Furthermore, a method for preparing a medical light-shielding and breathable double-layer curtain comprises the following preparation steps: (1) Place high-density polyester warp knitted fabric in a container, use deionized water as the spray medium, spray at a flow rate of 15-35 mL / min, and spray at 100°C for 40-50 min to obtain pretreated polyester fabric; (2) Open single-walled carbon nanotubes, 3-hydroxypropionic acid, and N,N-dimethylformamide were mixed in a mass ratio of 0.1-1:19-30:10-18, and ultrasonically dispersed at 400-600 W for 30 min. The mixture was reacted at 100-115 °C for 40-48 h, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran for three times, and dried at 70 °C for 6 h to obtain carboxylated single-walled carbon nanotubes. (3) Ultrasonic sensor probes were placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the two ends. A carboxylated single-walled carbon nanotube-deionized water dispersion with a mass fraction of 1-5% was sprayed on the pretreated polyester fabric at a spray flow rate of 5-10 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 10-20 min. The mixture was allowed to stand for 5 min, and then sprayed for another 10-20 min under the same conditions. The ultrasonic sensor probe was then removed. Anhydrous ethanol and tetrabutyl titanate were mixed in a mass ratio of 4 / 5 to obtain medium A. The remaining mass Mix 1 / 5 of anhydrous ethanol and deionized water, add ammonia water until the pH value of the solution is 7.5-8.2, and obtain medium B; spray medium A at a spray flow rate of 5-15 mL / min for 22-42 minutes, spray medium B at a spray flow rate of 3-8 mL / min for 5-11 minutes, heat to 30-40°C, continue spraying for 30-40 minutes, turn off the spray, heat to 70-80°C, keep warm for 2-3 hours, heat to 95°C, keep warm for 30 minutes, vacuum -0.06 MPa, dry at 50°C for 4 hours to obtain an antibacterial polyester shading layer; (4) After stacking the viscose fiber fabric and the antibacterial polyester shading layer in equal areas, a hydroentanglement process is performed. The first water pressure is 500 bar, the hydroentanglement time is 20 s, the second water pressure is 600 bar, the hydroentanglement time is 30 s, the third water pressure is 800 bar, the time is 10 s, and the fourth water pressure is 500 bar, the time is 30 s, to obtain a medical light-blocking and breathable double-layer curtain.
[0009] Furthermore, the preparation method of the open single-walled carbon nanotubes in step (2) is: placing the single-walled carbon nanotubes in a mixed acid solution with a mass of 50 times that of the single-walled carbon nanotubes, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid with a mass fraction of 68% is 3:1, reacting at 80°C for 12-24 hours, cooling to room temperature, filtering, rinsing with deionized water until the pH of the washing solution is 7, and drying at 120°C for 24 hours.
[0010] Furthermore, the diameter of the single-walled carbon nanotube is 0.8-5 nm.
[0011] Furthermore, in step (3), the mass ratio of anhydrous ethanol, tetrabutyl titanate and deionized water is 129:34:9.
[0012] Furthermore, in step (4), the jet aperture of the hydroentanglement process is 0.1-0.5 mm, the hydroentanglement speed is 20-40 m / s, and the direction is non-directional.
[0013] Furthermore, the viscose fiber fabric in step (4) is made of viscose fiber with an average length of 38 mm and an average fineness of 1.67 dtex, and a gram weight of 80-120 g / m 2 .
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention utilizes hydroentanglement to combine viscose fiber fabric and antibacterial polyester shading layer so that adjacent layers are bonded by entanglement between fibers, thereby improving the porosity of the partition curtain. The pressure, time and direction are changed each time the hydroentanglement is performed, so that a gradient pore structure is formed between the double-layer fabrics. The pressure difference along the diffusion channel caused by the change in pore size is beneficial to the transmission of gas and accelerates the transmission speed, thereby further optimizing the air permeability of the partition curtain.
[0015] The invention first performs a first thermal spray treatment on the high-density polyester warp-knitted base fabric to open the pores of the base fabric fibers and decompose some chain segments of the base fabric polyester fibers to form carboxyl groups. Then, a second spray treatment is performed. The expansion of the base fabric pores is conducive to the penetration of nano-scale carboxylated open single-walled carbon nanotubes. The single-walled carbon nanotubes are embedded in the inner wall of the fiber with gravity and spray external force to form a breathable channel to achieve the air permeability of the partition curtain. At the same time, the surface of the single-walled carbon nanotubes is hydrogen-bonded with the bottom, which is conducive to the fixation of the single-walled carbon nanotubes and titanium dioxide. In addition, during the infiltration process, the single-walled carbon nanotubes are uniformly and randomly arranged inside the fiber with the assistance of ultrasonic external force, and the openings are in different directions, so that the subsequent titanium dioxide deposition will not affect the base fabric. air permeability; then a third spray treatment is carried out, with tetrabutyl titanate and ethanol as the spray raw materials. Due to the mutual solubility of tetrabutyl titanate and anhydrous ethanol, anhydrous ethanol can quickly penetrate, driving tetrabutyl titanate into the fiber, chelating and coordinating with the single-walled carbon nanotubes and the carboxyl groups on the fiber surface, effectively delaying the hydrolysis and condensation of tetrabutyl titanate, which is conducive to the growth of uniform titanium dioxide particles. As the spray and reaction time increase, the chelate decomposes, overlaps with each other, and penetrates between the fibers. The deposition of titanium dioxide optimizes the conductivity of the single-walled carbon nanotubes, and at the same time forms a continuous conductive network with the help of titanium dioxide, thereby improving the antistatic property of the partition curtain. In addition, the single-walled carbon nanotubes and titanium dioxide form a physical barrier to achieve shading and antibacterial effects. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0017] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the medical light-shielding and breathable double-layer curtain prepared in the following examples are as follows: Light blocking: Take the embodiment and comparative example of equal size and test the light blocking rate according to AATCC-148-79.
[0018] Antistatic: Take the same size of the embodiment and the comparative example to test the surface charge density of the fabric according to GB / T12703.2 Antibacterial: The same size of the embodiment and the comparative example were taken to conduct antiviral activity test according to ISO18184, and the virus tested was influenza A virus.
[0019] Air permeability: Take the embodiment and comparative example of the same size to test the air permeability according to GB / T5453.
[0020] Example 1 (1) A high-density polyester warp knitted fabric with a polyester fiber specification of 56 dtex / 24F and a fabric transverse and longitudinal density of 70×100 strands / inch was placed in a container, and deionized water was used as a spray medium. The spray was performed at 100° C. and a spray flow rate of 15 mL / min for 40 minutes to obtain a pretreated polyester fabric; (2) placing a single-walled carbon nanotube with a diameter of 0.8 nm in a mixed acid solution with a mass 50 times that of the single-walled carbon nanotube, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid with a mass fraction of 68% is 3:1, reacting at 80°C for 12 hours, cooling to room temperature, filtering, rinsing with deionized water until the pH of the washing solution is 7, and drying at 120°C for 24 hours to obtain open single-walled carbon nanotubes; (3) Open single-walled carbon nanotubes, 3-hydroxypropionic acid, and N,N-dimethylformamide were mixed in a mass ratio of 0.1:19:10, and ultrasonically dispersed at 400 W for 30 min. The mixture was reacted at 100 °C for 40 h, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran for three times, respectively, and dried at 70 °C for 6 h to obtain carboxylated single-walled carbon nanotubes. (4) Ultrasonic sensor probes were placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the two ends. A 1% carboxylated single-walled carbon nanotube-deionized water dispersion was sprayed on the pretreated polyester fabric at a spray flow rate of 5 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 10 min. The fabric was allowed to stand for 5 min, and then sprayed for another 10 min under the same conditions. The ultrasonic sensor probe was then removed. Anhydrous ethanol and tetrabutyl titanate were mixed in an amount of 4 / 5 by mass to obtain medium A. The remaining mass of anhydrous ethanol was 1 / 5 by mass. Alcohol and deionized water are mixed, and ammonia water is added until the pH value of the solution is 7.5 to obtain medium B; after spraying medium A at a spray flow rate of 5 mL / min for 22 minutes, after spraying medium B at a spray flow rate of 3 mL / min for 5 minutes, the temperature is raised to 30°C, and spraying is continued for 30 minutes. The spray is turned off, the temperature is raised to 70°C, and the temperature is kept for 2 hours. The temperature is raised to 95°C, and the temperature is kept for 30 minutes. The vacuum degree is -0.06 MPa and the temperature is dried at 50°C for 4 hours to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9; (5) After stacking the viscose fiber fabric and the antibacterial polyester shading layer of equal area, a hydroentanglement process is performed. The first water pressure is 500 bar, the hydroentanglement time is 20 s, the second water pressure is 600 bar, the hydroentanglement time is 30 s, the third water pressure is 800 bar, the time is 10 s, and the fourth water pressure is 500 bar, the time is 30 s, to obtain a medical light-blocking and breathable double-layer partition curtain; the jet aperture of the hydroentanglement process is 0.1 mm, the hydroentanglement speed is 20 m / s, and the direction is non-directional.
[0021] Example 2 (1) A high-density polyester warp knitted fabric with a polyester fiber specification of 56 dtex / 24F and a fabric transverse and longitudinal density of 75×105 strands / inch was placed in a container, and deionized water was used as a spray medium. The spray was performed at 100° C. and a spray flow rate of 25 mL / min for 45 minutes to obtain a pretreated polyester fabric; (2) placing single-walled carbon nanotubes with a diameter of 2.9 nm in a mixed acid solution with a mass 50 times that of the single-walled carbon nanotubes, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid with a mass fraction of 68% is 3:1, reacting at 80°C for 18 hours, cooling to room temperature, filtering, rinsing with deionized water until the pH of the washing solution is 7, and drying at 120°C for 24 hours to obtain open single-walled carbon nanotubes; (3) Open single-walled carbon nanotubes, 3-hydroxypropionic acid, and N,N-dimethylformamide were mixed in a mass ratio of 0.5:25:14, and ultrasonically dispersed at 500 W for 30 min. The mixture was reacted at 108 °C for 44 h, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran for three times, respectively, and dried at 70 °C for 6 h to obtain carboxylated single-walled carbon nanotubes. (4) Ultrasonic sensor probes were placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the two ends. A 3% carboxylated single-walled carbon nanotube-deionized water dispersion was sprayed on the pretreated polyester fabric at a spray flow rate of 8 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 15 min. The mixture was allowed to stand for 5 min. After spraying for another 15 min under the same conditions, the ultrasonic sensor probe was removed. Anhydrous ethanol and tetrabutyl titanate were mixed in an amount of 4 / 5 by mass to obtain medium A. The remaining anhydrous ethanol and tetrabutyl titanate were mixed in an amount of 1 / 5 by mass to obtain medium A. Deionized water was mixed, and ammonia water was added until the pH value of the solution was 7.9 to obtain medium B; medium A was sprayed at a spray flow rate of 10 mL / min for 32 minutes, and medium B was sprayed at a spray flow rate of 5 mL / min for 8 minutes, and the temperature was raised to 35°C, and spraying continued for 35 minutes. The spray was turned off, and the temperature was raised to 75°C, and the temperature was kept for 2.5 hours. The temperature was raised to 95°C, and the temperature was kept for 30 minutes. The vacuum degree was -0.06 MPa and the temperature was 50°C for 4 hours to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water was 129:34:9; (5) After stacking the viscose fiber fabric and the antibacterial polyester shading layer of equal area, a hydroentanglement process is performed. The first water pressure is 500 bar, the hydroentanglement time is 20 s, the second water pressure is 600 bar, the hydroentanglement time is 30 s, the third water pressure is 800 bar, the time is 10 s, and the fourth water pressure is 500 bar, the time is 30 s, to obtain a medical light-blocking and breathable double-layer partition curtain; the jet aperture of the hydroentanglement process is 0.3 mm, the hydroentanglement speed is 30 m / s, and the direction is non-directional.
[0022] Example 3 (1) A high-density polyester warp knitted fabric with a polyester fiber specification of 56 dtex / 24F and a fabric transverse and longitudinal density of 80×110 strands / inch was placed in a container, and deionized water was used as a spray medium. The spray was performed at 100° C. and a spray flow rate of 35 mL / min for 50 minutes to obtain a pretreated polyester fabric; (2) placing a single-walled carbon nanotube with a diameter of 5 nm in a mixed acid solution with a mass fraction of 50 times that of the single-walled carbon nanotube, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid with a mass fraction of 68% is 3:1, reacting at 80°C for 24 hours, cooling to room temperature, filtering, rinsing with deionized water until the pH of the washing solution is 7, and drying at 120°C for 24 hours to obtain open single-walled carbon nanotubes; (3) Open single-walled carbon nanotubes, 3-hydroxypropionic acid, and N,N-dimethylformamide were mixed in a mass ratio of 1:30:18, and ultrasonically dispersed at 600 W for 30 min. The mixture was reacted at 115 °C for 48 h, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran for three times, and dried at 70 °C for 6 h to obtain carboxylated single-walled carbon nanotubes. (4) Ultrasonic sensor probes were placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the two ends. A 5% carboxylated single-walled carbon nanotube-deionized water dispersion was sprayed on the pretreated polyester fabric at a spray flow rate of 10 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 20 min. The fabric was allowed to stand for 5 min, and then sprayed for another 20 min under the same conditions. The ultrasonic sensor probe was then removed. Anhydrous ethanol and tetrabutyl titanate were mixed in an amount of 4 / 5 by mass to obtain medium A. The remaining anhydrous ethanol was mixed in an amount of 1 / 5 by mass to obtain medium A. , deionized water, add ammonia water until the solution pH is 8.2 to obtain medium B; spray medium A at a spray flow rate of 15mL / min for 42min, spray medium B at a spray flow rate of 8mL / min for 11min, heat to 40°C, continue spraying for 40min, turn off the spray, heat to 80°C, keep warm for 3h, heat to 95°C, keep warm for 30min, vacuum degree -0.06MPa, 50°C dry for 4h to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9; (5) After stacking the viscose fiber fabric and the antibacterial polyester shading layer of equal area, a hydroentanglement process is performed. The first water pressure is 500 bar, the hydroentanglement time is 20 s, the second water pressure is 600 bar, the hydroentanglement time is 30 s, the third water pressure is 800 bar, the time is 10 s, and the fourth water pressure is 500 bar, the time is 30 s, to obtain a medical light-blocking and breathable double-layer partition curtain; the jet aperture of the hydroentanglement process is 0.5 mm, the hydroentanglement speed is 40 m / s, and the direction is non-directional.
[0023] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is omitted, and step (4) is changed to: ultrasonic sensor probes are placed on the left and right ends of a high-density polyester warp knitted fabric with a polyester fiber specification of 56 dtex / 24F and a fabric transverse and longitudinal density of 75×105 strands / inch, with a distance of 5 cm between the left and right ends, and a carboxylated single-walled carbon nanotube-deionized water dispersion with a mass fraction of 3% is sprayed on the high-density polyester warp knitted fabric, with a spray flow rate of 8 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 15 minutes, and then allowed to stand for 5 minutes. After spraying for another 15 minutes under the same conditions, the ultrasonic sensor probe is removed; a dispersion of 4 / 5 mass carbon nanotubes is sprayed on the high-density polyester warp knitted fabric. Mix anhydrous ethanol and tetrabutyl titanate to obtain medium A; mix the remaining mass of 1 / 5 anhydrous ethanol and deionized water, add ammonia water until the solution pH is 7.9, and obtain medium B; spray medium A at a spray flow rate of 10mL / min for 32min, spray medium B at a spray flow rate of 5mL / min for 8min, heat to 35°C, continue spraying for 35min, turn off the spray, heat to 75°C, keep warm for 2.5h, heat to 95°C, keep warm for 30min, vacuum degree -0.06MPa, 50°C dry for 4h to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9. The remaining steps are the same as in Example 2.
[0024] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (3) is changed to: single-walled carbon nanotubes with a diameter of 2.9 nm, 3-hydroxypropionic acid, and N,N-dimethylformamide are mixed in a mass ratio of 0.5:25:14, ultrasonically dispersed at 500 W for 30 minutes, reacted at 108° C. for 44 hours, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran three times respectively, and dried at 70° C. for 6 hours to obtain carboxylated single-walled carbon nanotubes. The remaining steps are the same as those in Example 2.
[0025] Comparative Example 3 The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: spray a carboxylated single-walled carbon nanotube-deionized water dispersion with a mass fraction of 3% on the pretreated polyester fabric, spray for 15 minutes at a spray flow rate of 8 mL / min, let it stand for 5 minutes, and spray for another 15 minutes under the same conditions; mix 4 / 5 of the mass of anhydrous ethanol and tetrabutyl titanate to obtain medium A; mix the remaining mass of anhydrous ethanol and deionized water with a mass of 1 / 5, and add ammonia water until the solution pH is 7 .9, to obtain medium B; after spraying medium A at a spray flow rate of 10mL / min for 32min, after spraying medium B at a spray flow rate of 5mL / min for 8min, the temperature was raised to 35°C, and spraying was continued for 35min. The spray was turned off, the temperature was raised to 75°C, and the temperature was kept warm for 2.5h. The temperature was raised to 95°C, and the temperature was kept warm for 30min. The antibacterial polyester shading layer was obtained by drying at a vacuum degree of -0.06MPa and 50°C for 4h. The mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9.
[0026] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that there is no step (3), and step (4) is changed to: ultrasonic sensor probes are placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the left and right ends, and a 3% open single-walled carbon nanotube-deionized water dispersion is sprayed on the pretreated polyester fabric at a spray flow rate of 8 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 15 minutes, and then allowed to stand for 5 minutes. After spraying for another 15 minutes under the same conditions, the ultrasonic sensor probe is removed; anhydrous ethanol and tetrabutyl titanate are mixed in an amount of 4 / 5 by mass to obtain medium A; the remaining The remaining mass of 1 / 5 of anhydrous ethanol and deionized water is mixed, and ammonia water is added until the pH of the solution is 7.9 to obtain medium B; after spraying medium A at a spray flow rate of 10 mL / min for 32 minutes, spraying medium B at a spray flow rate of 5 mL / min for 8 minutes, heating to 35°C, continuing to spray for 35 minutes, turning off the spray, heating to 75°C, keeping warm for 2.5 hours, heating to 95°C, keeping warm for 30 minutes, vacuum degree -0.06MPa, 50°C drying for 4 hours to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9. The remaining steps are the same as in Example 2.
[0027] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that step (4) is different. Step (4) is changed to: ultrasonic sensor probes are placed at the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the left and right ends, and a carboxylated single-walled carbon nanotube-deionized water dispersion with a mass fraction of 3% is sprayed on the pretreated polyester fabric. The spray flow rate is 8 mL / min, the ultrasonic power is 300 W, and the ultrasonic frequency is 20 kHz. Spray for 15 minutes, let it stand for 5 minutes, and spray for another 15 minutes under the same conditions. The vacuum degree is -0.06 MPa and the temperature is 50°C. Dry for 4 hours to obtain an antibacterial polyester shading layer; the mass ratio of anhydrous ethanol, tetrabutyl titanate, and deionized water is 129:34:9. The remaining steps are the same as in Example 2.
[0028] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that step (5) is different. Step (5) is changed to: after stacking the viscose fiber fabric and the antibacterial polyester shading layer of equal area, hydroentanglement is performed, the first hydroentanglement time is 20 seconds, the second hydroentanglement time is 30 seconds, the third hydroentanglement time is 10 seconds, and the fourth hydroentanglement time is 30 seconds, so as to obtain a medical light-shielding and breathable double-layer partition curtain; the jet aperture of the hydroentanglement process is 0.3 mm, the hydroentanglement speed is 30 m / s, the direction is non-directional, and the hydroentanglement pressure is 600 bar. The remaining steps are the same as those in Example 2.
[0029] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that step (5) is different. Step (5) is changed to: after stacking the viscose fiber fabric and the antibacterial polyester shading layer with equal areas, hydroentanglement is performed, the first water pressure is 500 bar, the second water pressure is 600 bar, the third water pressure is 800 bar, and the fourth water pressure is 500 bar, so as to obtain a medical light-shielding and breathable double-layer partition curtain; the jet aperture of the hydroentanglement process is 0.3 mm, the hydroentanglement speed is 30 m / s, the direction is non-directional, and the hydroentanglement time is 30 s. The remaining steps are the same as Example 2.
[0030] Comparative Example 8 The difference between Comparative Example 8 and Example 2 is that step (5) is different. Step (5) is changed to: after stacking the viscose fiber fabric and the antibacterial polyester shading layer with equal areas, hydroentanglement is performed, the first water pressure is 500 bar, the hydroentanglement time is 20 seconds, the second water pressure is 600 bar, the hydroentanglement time is 30 seconds, the third water pressure is 800 bar, the time is 10 seconds, and the fourth water pressure is 500 bar, the time is 30 seconds, and the medical light-shielding and breathable double-layer partition curtain is obtained; the jet aperture of the hydroentanglement process is 0.3 mm, the hydroentanglement speed is 30 m / s, and the direction is vertically downward. The remaining steps are the same as Example 2.
[0031] Effect example Table 1 below shows the performance analysis results of the medical light-shielding and breathable double-layer curtains of Examples 1 to 3 of the present invention and Comparative Examples 1 to 8.
[0032] Table 1
[0033] From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention introduces carboxyl groups into the polyester base fabric through thermal hydrolysis, and then embeds the open carboxylated nano-scale carbon nanotubes into the bottom fibers, and disperses them evenly inside the fibers through ultrasound to improve the air permeability of the partition curtain, and then utilizes carboxyl chelated tetrabutyl titanate to decompose and overlap to form a continuous titanium dioxide-carbon nanotube network to improve the light-shielding and antibacterial properties of the partition curtain, and then utilizes viscose fiber fabric to change the water entanglement pressure, time, and direction each time to form a gradient pore structure between the double-layer fabrics, thereby further optimizing the air permeability of the partition curtain.
[0034] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A medical light-shielding and breathable double-layer curtain, characterized in that: The medical light-blocking and breathable double-layer partition curtain has an antibacterial polyester light-blocking layer as a base fabric and a viscose fiber fabric as a surface layer, and is produced through multiple water-spunlace processes.
2. A medical light-shielding and breathable double-layer curtain according to claim 1, characterized in that: The antibacterial polyester shading layer is made of high-density polyester warp-knitted fabric after three spraying treatments.
3. A medical light-shielding and breathable double-layer curtain according to claim 2, characterized in that: The polyester fiber specification in the high-density polyester warp-knitted fabric is 56dtex / 24F, and the transverse and longitudinal densities of the fabric are (70-80)×(100-110) strands / inch.
4. The medical light-shielding and breathable double-layer curtain according to claim 2, characterized in that: The first spray treatment uses deionized water as the spray medium and sprays at a certain temperature; the second spray treatment uses carboxylated single-walled carbon nanotube-deionized water dispersion as the spray medium and sprays intermittently under ultrasound; the third spray treatment first uses tetrabutyl titanate ethanol as the spray medium, sprays for a period of time, and then uses ethanol-water-ammonia water as the spray medium and sprays at different temperatures.
5. A method for preparing a medical light-shielding and breathable double-layer curtain, characterized in that: The method comprises the following preparation steps: (1) Place high-density polyester warp knitted fabric in a container, use deionized water as the spray medium, spray at a flow rate of 15-35 mL / min, and spray at 100°C for 40-50 min to obtain pretreated polyester fabric; (2) Open single-walled carbon nanotubes, 3-hydroxypropionic acid, and N,N-dimethylformamide were mixed in a mass ratio of 0.1-1:19-30:10-18, and ultrasonically dispersed at 400-600 W for 30 min. The mixture was reacted at 100-115 °C for 40-48 h, cooled to room temperature, filtered, and the filter cake was washed with ethanol and tetrahydrofuran for three times, and dried at 70 °C for 6 h to obtain carboxylated single-walled carbon nanotubes. (3) Ultrasonic sensor probes were placed on the left and right ends of the pretreated polyester fabric, with a distance of 5 cm between the two ends. A carboxylated single-walled carbon nanotube-deionized water dispersion with a mass fraction of 1-5% was sprayed on the pretreated polyester fabric at a spray flow rate of 5-10 mL / min, an ultrasonic power of 300 W, and an ultrasonic frequency of 20 kHz for 10-20 min. The mixture was allowed to stand for 5 min, and then sprayed for another 10-20 min under the same conditions. The ultrasonic sensor probe was then removed. Anhydrous ethanol and tetrabutyl titanate were mixed in a mass ratio of 4 / 5 to obtain medium A. The remaining mass Mix 1 / 5 of anhydrous ethanol and deionized water, add ammonia water until the pH value of the solution is 7.5-8.2, and obtain medium B; spray medium A at a spray flow rate of 5-15 mL / min for 22-42 minutes, spray medium B at a spray flow rate of 3-8 mL / min for 5-11 minutes, heat to 30-40°C, continue spraying for 30-40 minutes, turn off the spray, heat to 70-80°C, keep warm for 2-3 hours, heat to 95°C, keep warm for 30 minutes, vacuum -0.06 MPa, dry at 50°C for 4 hours to obtain an antibacterial polyester shading layer; (4) After stacking the viscose fiber fabric and the antibacterial polyester shading layer in equal areas, a hydroentanglement process is performed. The first water pressure is 500 bar, the hydroentanglement time is 20 s, the second water pressure is 600 bar, the hydroentanglement time is 30 s, the third water pressure is 800 bar, the time is 10 s, and the fourth water pressure is 500 bar, the time is 30 s, to obtain a medical light-blocking and breathable double-layer curtain.
6. The method for preparing a medical light-shielding and breathable double-layer curtain according to claim 5, characterized in that: The preparation method of the open single-walled carbon nanotubes in step (2) is as follows: placing the single-walled carbon nanotubes in a mixed acid solution with a mass of 50 times that of the single-walled carbon nanotubes, wherein the volume ratio of concentrated sulfuric acid to concentrated nitric acid with a mass fraction of 68% is 3:1, reacting at 80°C for 12-24 hours, cooling to room temperature, filtering, rinsing with deionized water until the pH of the washing solution is 7, and drying at 120°C for 24 hours.
7. The method for preparing a medical light-shielding and breathable double-layer curtain according to claim 6, characterized in that: The diameter of the single-walled carbon nanotube is 0.8-5 nm.
8. The method for preparing a medical light-shielding and breathable double-layer curtain according to claim 5, characterized in that: The mass ratio of anhydrous ethanol, tetrabutyl titanate and deionized water in step (3) is 129:34:
9.
9. The method for preparing a medical light-shielding and breathable double-layer curtain according to claim 5, characterized in that: The jet aperture of the hydroentanglement process in step (4) is 0.1-0.5 mm, the hydroentanglement speed is 20-40 m / s, and the direction is non-directional.
10. The method for preparing a medical light-shielding and breathable double-layer curtain according to claim 5, characterized in that: The viscose fiber fabric in step (4) is made of viscose fiber with an average length of 38 mm and an average fineness of 1.67 dtex, and a gram weight of 80-120 g / m 2 .